TYPOLOGY ANALYSIS AND CONCENTRATION MSMES IN THE CENTRAL LAMPUNG REGENCY - Resha Moniyana Putri; Vitriyani Tri Purwaningsih; Muhammad Husaini; Emi Maimunah; Akbar Setiawan; Citra Sofira (Politeknik Bisnis Indonesia, 2024)
The role of MSME’s (Micro Small and Medium Enterprises) is certainly very helpful to the economy of Central Lampung Regency. The first highest average contribution of the sector that contributes to the economy according to business field is the agricultural sector (A), plantations and fisheries which has the highest percentage value with 34.17%, while the second highest average contribution is the processing industry sector (C) with the average percentage is 22.92%. This indicates that the economy of Central Lampung is dominated by the primary sector and its processing industry. The condition of other sectors contributes 1-10%, where other sectors are expected to have the potential to become sectors that contribute to the economy, such as the construction sector (F) at 11.16% and the wholesale trade (G), retail and repair sectors at 10.56% . The processing industry and development in the industrial sector contribute greatly to stimulating economic growth and are able to provide added value, especially for raw materials, employment and expanding business opportunities to improve community welfare. The research results show that the distribution of MSMEs in Central Lampung Regency is dominated by MSMEs with industry. food and drink with the District of Terbanggi Besar being the highest contributor to the number of MSMEs in Central Lampung Regency. The distribution of worker concentration in MSMEs uses the Hoover Balassa Index method where the results of the HBI show that almost all workers working in MSMEs in Central Lampung are not concentrated in the dominant MSMEs.